Talking, Walking and Making in Cheetham Park: Reflecting on Everyday Participation as a Method and the Failure of an Interdisciplinary Commons - Gilmore, Abigail; Lang, Luciana (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This article presents a case study of an inter-disciplinary project in a small Victorian public park in Manchester. The project was a collaboration between Manchester Jewish Museum and the University of Manchester, which aimed to foster participation and a sense of ownership amongst local residents, park users and museum visitors, and create a sustainable social infrastructure to look after this particular public space. Academic researchers and an Artist-in-Residence worked together using a range of participatory methods we summarise as ‘talking, walking and making’. Here we reflect critically through the framework of ‘the commons’ to identify how and why the project failed to produce its intended outcomes. We focus on one object, the park’s shelter; and one event, the park’s 130th anniversary, as ‘boundary objects’ (Star & Griesemer, 1989) to reveal the dissonant world-views of the project’s participants, critically assess its participatory methods, and offer reflexivity from a multidisciplinary perspective.